Consumers ability to discern food quality under blind conditions - Pasta, C.; Cortese, G.; Marino, et al., G. (Progress in Nutrition, 2013)
Purpose: This study aims to investigate consumers ability to discern foodproduct quality in absence of information compared to mass products.Design/methodology/approach: Milk types were selected in order to satisfytwo dimensions: fat content and quality difference. Two experimentswere run: in the first standardized or mass milks (Ultra-High-Temperature/UHT) were compared considering the fat dimension (3.5% vs1.8%), whereas in the second experiment quality milks were comparedaccording to quality attributes (Whole Fresh High Premium QualityMilk vs Raw Milk). In both experiments, consumers performed a triangletest and filled a computerized form indicating the odd milk, theirpreference, habits of consumption as well as demographic information.Findings: Consumers both inability and ability to spot the odd milk wasnot affected by preference or consumption habits. Results showed that inabsence of information consumers easily detected high quality productsrather than standardized or mass products. In fact, between standardized(UHT milk types) 64% of participants did not spot correctly the oddmilk (p